Post-traumatic stress disorder after acubarotrauma: a case report - Fitkalo Олег (Psychosomatic Medicine and General Practice, 2024)
Abstract. The article describes a clinical case of post-traumatic stress disorder and features of its course caused by a mine-explosive injury, diagnosis and treatment of this disease. On the basis of the patient’s complaints, medical history, neurological and mental status data, as well as the results of a neurophysiological and neuropsychological examination, it was found that after the last treatment, for a period of 2 months, the patient’s condition worsened: complaints of intense emotional fluctuations, manifested by anxiety, sleep disorders and logoneurosis (suffocation) became permanent, increased excitement was maintained both during sleep and during wakefulness. At the same time, clonic jerks of the right arm and left leg, which sometimes had the appearance of tonic-clonic seizures, were added to the general symptoms of PTSD (flashbacks, overwhelming memories with nightmare dreams, and avoidance of crowds). Physiological manifestations of asthenic syndrome were characterized by pain in the region of the heart, constant fluctuations in pressure. In addition, a relaxation technique using binaural sounds and photostimulation is proposed as a natural positive stimulation of the senses (sight and hearing) to increase the production of "hormones of happiness". After conducting several sessions of audiovisual stimulation, positive dynamics were observed in the form of improved sleep and a reduction in the high level of stuttering. After the session, the patient felt more relaxed and was able to effectively discuss personal problems with the doctor. A relaxation methodology using the "Photosonix Nova Pro 100 Mind Machine" device is proposed, which provides an incomparable opportunity to control the psycho-emotional state of the patient.